The Conundrum of Labyrinthitis Ossificans: An Etiology-Based Case Comparison and Review of Literature - Nidhin Das K; Vidhu Sharma; Amit Goyal (Turkish Archives of Otorhinolaryngology, 2023)

(untitled)
Labyrinthitis ossificans is the formation of pathological new bone within the membranous labyrinth of the inner ear due to various local and systemic pathologies. Most commonly it occurs as a sequelae of meningitis spreading to the labyrinth, from the subarachnoid space via the cochlear aqueduct and the internal auditory canal. We are comparing three different etiological presentations of labyrinthitis ossificans; namely, tympanogenic, meningitic, and traumatic, together with their management in the light of recent advances.